Effectiveness of Low-Level Laser Therapy in reducing postoperative pain after dental implant surgery: A randomized clinical trial - Basualdo Allende, Javier; Caviedes, Rodrigo; von Marttens, Alfredo; Ramírez, Francisca González; Piña, Iara Vargas; Kuga, Milton [UNESP]; Fernández, Eduardo (Elsevier, 2024)
Background: A clinical trial was conducted to measure the effectiveness of a combined wavelength of 660 nm and 808 nm Low-Level Laser Therapy (LLLT) in reducing postoperative pain in partially and totally edentulous patients who underwent dental implant surgery. Materials and Methods: The study included 20 blinded individuals divided in a randomized split-mouth fashion; the experimental group in one hemiarch and the control group in the other hemiarch. The experimental group received a total of 22.5 Joules (J) of LLLT divided into 5 points per implant immediately after surgery. The control group received a placebo treatment. At 24 h, 72 h, and 7 days, a blinded surveyor administered a pain questionnaire using a Numerical Rating Scale (NRS) combined with a Verbal Rating Scale (VRS) to assess pain onset after surgery, duration of the first pain episode, and pain evolution. Group data were analyzed with an ANOVA test for repeated measures and a paired t-test at defined time intervals. Results: The experimental group showed a significant decrease in postoperative pain at 24 h and at 72 h for fully edentulous patients. There was a non-significant difference in the duration of the first pain episode. The mean pain levels decreased over time for both the experimental and control treatments, but only statistically significantly for the experimental group in the 24–72 h and 24 h to 7 days intervals. The same was true for the control group when comparing 24 and 72 h and between 24 h and 1 week. The time range between 72 h and 1 week showed no statistically significant differences. Conclusion: Within the limitations of this study, a single dose of 22.5 J LLLT per implant helps to decrease postoperative pain in dental implant surgery at 24 h for partially edentulous patients and at 24 and 72 h for fully edentulous patients.
Keywords: Clinical trial; Dental implant surgery; Low-Level Laser Therapy; Pain management; Postoperative pain